2001
DOI: 10.1055/s-2001-18126
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided Aspiration of Brain Abscesses Through a Single Burr Hole

Abstract: Surgical aspiration and/or drainage of brain abscesses is considered to be the first-line treatment for abscesses larger than 25 mm. This is ususally performed with the aid of CT-guided stereotaxy. A method of ultrasound guidance is presented that allows a single burr hole approach with real-time imaging of the whole procedure. A bayonet-like shaped ultrasound probe with tip dimension of 8 x 8 mm only (EUP-NS 32, Hitachi/Ecoscan) with frequencies of 3.5 and 5 MHz is used. After placement of a burr hole the tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…In addition, the use of DWI requires the presence of a neuroradiologist, and unfortunately not all hospitals are equipped with such a team, leading to a search for other methods of diff erential diagnosis. Recently, stereotactic abscess aspiration has become the treatment of choice particularly in deep-seated abscesses, as this technique permits microbiological diagnosis and drainage of the abscess fl uid with reduced mortality and morbidity [2,3,11,15,22,35] . Many authors report the use of neuronavigation instead of stereotactic frame-based procedures for the drainage of brain abscess, and similar results were obtained with these two techniques [2,6,20,26] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the use of DWI requires the presence of a neuroradiologist, and unfortunately not all hospitals are equipped with such a team, leading to a search for other methods of diff erential diagnosis. Recently, stereotactic abscess aspiration has become the treatment of choice particularly in deep-seated abscesses, as this technique permits microbiological diagnosis and drainage of the abscess fl uid with reduced mortality and morbidity [2,3,11,15,22,35] . Many authors report the use of neuronavigation instead of stereotactic frame-based procedures for the drainage of brain abscess, and similar results were obtained with these two techniques [2,6,20,26] .…”
Section: Discussionmentioning
confidence: 99%
“…This technique has been used as first-line treatment for abscesses larger than 25 mm [18]. The main drawback of this technique is that aspiration of the abscess usually needs to be repeated as total removal of pus is rarely possible in a single procedure [14].…”
Section: Discussionmentioning
confidence: 99%
“…2 Strowitzki et al recommended ultrasound-guided aspiration of brain abscess through a single burr hole as first-line treatment for abscesses larger than 25 mm. 3 Based on CT staging, Srinivasan et al treated 37 cases of encapsulated brain abscess with repeated elective aspiration through a burr hole and intracavity application of antibiotics on alternate days, until two consecutive negative aspirations were obtained; the mortality rate was 2.7 per cent and the morbidity rate 8.3 per cent. 8 Brydon and Hardwidge concluded that burr hole aspiration with regular CT was a satisfactory method of treatment for cerebellar abscess.…”
Section: Discussionmentioning
confidence: 99%